PENGARUH PENGGUNAAN DOMPET MINI BELANJA PADA PEMBELAJARAN BAHASA INDONESIA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV SD - Ruth Silvia Sinaga; Bernadus Wahyudi Joko Santoso; Haryadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using a mini shopping wallet on the learning outcomes of fourth-grade students in Indonesian Language subject. The background of this research is the low interest and understanding of students in writing, often making errors and lacking the courage to express ideas in writing. This quantitative research used an experimental method with a One Group Pretest-Posttest Design. The population was all fourth-grade students of Gugus 1 Tarutung Elementary School, and the sample was determined using purposive sampling, resulting in SDS HKBP Pearaja Tarutung as the experimental class. Data collection techniques involved multiple-choice questions in the form of pre-test and post-test. Data analysis used descriptive and inferential statistics, including the t-test. The results of the pre-test and post-test t-test showed a tcount of 2.032 and a ttable of 1.68, leading to the conclusion that there is an influence of the use of a mini shopping wallet on the learning outcomes of fourth-grade students. The mean pre-test score was 42.857, and the mean post-test score was 70.85. The use of the mini shopping wallet, which is a concrete medium in the form of toy money, provides real learning experience and effectively increases student learning outcomes, especially in understanding the concept of writing currency values.